Efficient production of phenyllactic acid in Escherichia coli via metabolic engineering and fermentation optimization strategies - Wu, Weibin; Chen, Maosen; Li, Chenxi; Zhong, Jie; Xie, Rusheng; Pan, Zhibin; Lin, Junhan; Qi, Feng (Frontiers in Microbiology, 2024)
Phenyllactic acid (PhLA), an important natural organic acid, can be used as a biopreservative, monomer of the novel polymeric material poly (phenyllactic acid), and raw material for various medicines. Herein, we achieved a high-level production of PhLA in Escherichia coli through the application of metabolic engineering and fermentation optimization strategies. First, the PhLA biosynthetic pathway was established in E. coli CGSC4510, and the phenylalanine biosynthetic pathway was disrupted to improve the carbon flux toward PhLA biosynthesis. Then, we increased the copy number of the key genes involved in the synthesis of the PhLA precursor phenylpyruvic acid. Concurrently, we disrupted the tryptophan biosynthetic pathway and enhanced the availability of phosphoenolpyruvate and erythrose 4-phosphate, thereby constructing the genetically engineered strain MG-P10. This strain was capable of producing 1.42 ± 0.02 g/L PhLA through shake flask fermentation. Furthermore, after optimizing the dissolved oxygen feedback feeding process and other conditions, the PhLA yield reached 52.89±0.25 g/L in a 6-L fermenter. This study successfully utilized metabolic engineering and fermentation optimization strategies to lay a foundation for efficient PhLA production in E. coli as an industrial application.